Assistência fonoaudiológica domiciliar na cidade de São Paulo: reflexões sobre o trabalho e o fazer terapêutico - Santos, Patrícia Rocha dos (2023)
Home care (HC) is understood as a healthcare model in which procedures are performed in the patient's home and include the family and caregivers as active participants in healthcare actions. HC encompasses different types or modalities of care: home visits, home hospitalization, and home therapy. In this context, the establishment of a specific setting is suggested, in which professionals are exposed to the different aspects and practices outside the usual clinical environments (such as offices, outpatient clinics, and hospitals), while also addressing issues between professionals and caregivers/family members in the provision of care. HC is provided by the Unified Health System (SUS) through Primary Care and the home care service, as well as by private health insurance through contracts with private companies and individuals, directly arranged with the patient/family. This study aims to understand the role of speech-language pathologists in this universe, focusing on the city of São Paulo. The method used consisted of two complementary strategies: an online questionnaire responded by 136 speech-language pathologists practicing in São Paulo, which allowed for profiling the services provided, professional relationships, basic working conditions, and the level of satisfaction of professionals with this type of practice; the second strategy involved further reflection on the topics addressed in the questionnaire through a Focus Group. The research concluded that speech-language pathologists working in private HC feel a lack of institutional support (professional associations, public policies, and specific regulations) in relation to the HC healthcare market. Despite the challenges inherent to HC practice, speech-language pathologists, in general, feel engaged and relatively satisfied with their work in this mode of healthcare delivery. From a therapeutic perspective, the caregiving process and the home setting evoke questions and peculiarities that, if well addressed, can be transformed into potential for healthcare provision